Lifetime Trauma Exposure and Posttraumatic Stress Disorder Among African Americans and Black Caribbeans by Sex and Ethnicity - Gran-Ruaz, Sophia Maria; Taylor, Robert Joseph; Jacob, Grace; Williams, Monnica T. (Frontiers in Psychiatry, 2022)
OBJECTIVE: Posttraumatic stress disorder (PTSD) is a debilitating disorder requiring timely diagnosis and treatment, with special attention needed for Black populations in the U.S. Yet, stakeholders often fail to recognize Black communities’ heterogeneous ethnic composition, thus not allowing diverse sociocultural realities to inform PTSD interventions. This study aims to characterize sex and ethnic differences in lifetime trauma exposure, lifetime PTSD diagnosis and symptoms, and help-seeking among the African Americans and Black Caribbeans in the U.S. METHOD: This study relied on data from the National Survey of American Life 2001-2003 (NSAL) to investigate the lifetime exposure to traumatic events and prevalence of a clinical PTSD diagnosis based on the DSM-IV among African American (n=3,570) and Black Caribbean (n=1,623) adults. 44.5% of respondents were men and 55.5% were female. Logistic regression was utilized to investigate the impact of traumatic events on PTSD. RESULTS: Several ethnic and sex differences in exposure to potentially traumatic events were identified. African American respondents were more likely to experience spousal abuse and toxin exposure than their Black Caribbean counterparts. Black Caribbeans reported higher lifetime exposure to muggings, natural disasters, harsh parental discipline, being a civilian living in terror and/or being a refugee than African American respondents. Specific to sex, Black men reported more events of combat, a peacekeeper/relief worker, being mugged, toxin exposure, seeing atrocities, and/or injuring someone. Black women were more likely to have been rape/sexual assault and/or intimate partner violence victims. The assaultive violence trauma type was most predictive of lifetime PTSD diagnosis among Black Americans. African American women were more likely to report PTSD symptoms than men, with almost no significant differences in Black Caribbean men and women. Approximately half of Black Americans sought help for their worst traumatic event, commonly engaging family/friends, psychiatrists, and mental health professionals. Further, there were almost no ethnic and sex differences related to professional and non-professional help sought. CONCLUSIONS: Future PTSD-related research should aim to characterize the heterogenous experiences of potentially traumatic events within different Black communities. Clinicians working with Black clients should strive to understand the limitations within their tools/interventions in meeting the needs of diverse groups.